MENELISIK PERAN KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA - Manuari, Ida Ayu Ratih; Devi, Ni Luh Nyoman Sherina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study aims to examine and analyze the effect of financial performance, firm size and investment opportunity set on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange. The number of samples in this study were 20 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The results show that liquidity, profitability and firm size have a positive effect on dividend policy. Solvency and investment opportunity set have a negative effect on dividend policy in Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2019.